Efficacy and safety of nivolumab plus ipilimumab in gastrointestinal cancers: a systematic review and meta-analysis - Dai, Bowen; Jiang, Jiaping; Yu, Xiaoyu; Zhan, Haihua; Hu, Zhengchuan (Frontiers in Oncology, 2025)
IntroductionGastrointestinal (GI) cancers represent a significant global health burden, and the need for more effective treatment options is exceptionally pressing. The present meta-analysis aimed to explore the efficacy and safety of the combination of nivolumab and ipilimumab in treating GI cancers.MethodsA systematic search of four databases (PubMed, Embase, Web of Science, and Cochrane Library) was conducted for articles on the treatment of GI cancers with nivolumab combined with ipilimumab, published from 2014 up to 30 August 2024. The inclusion criteria were designed according to the principles of Participants, Intervention, Control, Outcomes, and Study (PICOS). The control group was chemotherapy or nivolumab monotherapy or nivolumab in combination with other drugs. We extracted data from 10 randomized controlled trials and utilized a random effects model to assess the objective response rate (ORR), median progression-free survival (mPFS), median overall survival (mOS), median duration of response (mDOR), and treatment-related adverse events (TRAEs). The data analysis was conducted using Review Manager version 5.4 and Stata version 12.0.ResultsOverall, the combination of nivolumab and ipilimumab demonstrated superior outcomes, including a higher ORR (OR = 1.69, P = 0.01), prolonged mOS (MD = 1.74, P = 0.04) and extended mDOR (MD = 5.64, P < 0.00001) compared to the control group. Subgroup analysis demonstrated that the ORR (OR = 1.75, P = 0.02) and mOS (MD = 5.02, P = 0.003) were significantly improved in patients with esophageal cancer. Notably, the ORR in patients with biliary cancer was significantly lower (OR = 0.11, P = 0.04). Additionally, the ORR was significantly higher in the NIVO1 + IPI3group (OR = 2.82, P = 0.01) and NIVO3 + IPI1 group (OR = 1.62, P = 0.01). Regarding safety, there was no statistically significant difference between the combination regimen and the control group in terms of any grade (OR = 0.72, P = 0.26) or grade 3-4 TRAEs (OR = 1.36, P = 0.14).ConclusionsNivolumab in combination with ipilimumab demonstrated significant efficacy in GI cancers (especially esophageal cancer) without causing more adverse reactions. However, its efficacy in biliary cancer still needs to be further proven.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024590994.